THE IMPLEMENTATION OF INDUCTIVE APPROACH IN PRE-INTERMEDIATE STRUCTURE SUBJECT TO ENGLISH EDUCATION STUDY PROGRAM STUDENTS PGRI UNIVERSITY OF YOGYAKARTA - Endahati, Nafisah (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
Abstract The research aims at describing the implementation of inductive approach in pre-intermediate structure subject to English Education Study Program students. It describes how the response of the implementation of inductive approach through communicative activities to students of English Education Study Program, Faculty of Teacher Training and Education, PGRI University of Yogyakarta. The research was done qualitatively. It included some actions. The actions were activities of teaching and learning processes by implementing inductive approach through some communicative activities in the classroom. The subject of this research was the students of English Education Study Program, Faculty of Teacher Training and Education, PGRI University of Yogyakarta. The research data was analyzed qualitatively by using deep observation and interview. The result was represented descriptively. The result of the research was that the implementation of inductive approach through the communicative activities can (a) train students to be familiar with the rule of discovery; (b) exploit students’ greater degree of cognitive depth, (c) make the students are more active rather than being passive in the process, (d) involve students to collaboratively do problem solving, (e) involve students to get opportunity for extra language practice. Key words: inductive approach, pre-intermediate structure, communicative activities